Peran Pembimbing Akademik terhadap Pembentukan Karakter Mahasiswa - Agus Partawibawa; Syukri Fathudin; Achmad Widodo (Faculty of Engineering, Universitas Negeri Yogyakarta, 2014)
The objectives of this study were (1) to determine the roles of the academic supervisors in the students’ characters development, and (2) to analysethe factors affecting the academic supervisors’ roles in the students’ characters development at the Department of Automotive Engineering Education. This study employed the survey research method. It was conducted at the Department of Automotive Engineering Education, the Faculty of Engineering, State University ofYogyakarta. The data was analysed using descriptive analysis. The results showed the academic supervisors have positive impact on the students characters development in the aspects of education and teaching, research, and community services, (2) the factors affecting the academic supervisors’ roles in the students’ characters development are (a) the different levels of the students’ maturity, it can be solved by improving the students’ mind set, (b) psychological, socioemotional,and cultural differences. The solutions are continuing guidance through classes, workshops and private consultations, (3) The students perceivethat the role of the academic supervisors in their characters developmenthave positive impacts on the learning process, examinations, and academic services.